SISTEM PENYEDIAAN AIR MINUM DI DESA REJASA KECAMATAN PENEBEL KABUPATEN TABANAN - I Ketut Nuraga; I Komang Agus Ariana (Jurnal Ilmiah Telsinas, 2018)
Rejasa Village at Tabanan regency is the village were classified into the critical watersource especially for real water (domestic & non-domestic), including 4 (four) sub-villages : RejasaKaja, Rejasa Kelod, Pacut & Kelembang.To handle the critical water, water sources from other villages can be used such as the Bejiwater source in Pitra village of Penebel district. The expected water source discharge around 7.50 lt/s,and it’s confirmed to be able to fulfill the drinking water requirement of Rejasa village citizens until therequirement projection in the year 2040 for around 5.0 lt/s.The water flow from Beji water source in Pitra to the connection system to the reservoir withthe gravity flow system. The water availability is separated into 4 sub-systems, which are the RejasaKaja reservoir with volume design of 200 m3, the Rejasa Kelod reservoir (V = 175 m3), the Pacutreservoir (V = 100 m3), and the Kelembang reservoir (V = 100 m3).